AB0455 Disease duration, but not rheumatoid factor status, impacts clinical response in adalimumab-treated rheumatoid arthritis patients with an inadequate response to standard dmard therapy: Subgroup analysis of the DE020 continuation trial. (23rd January 2014) - Furst, D.E.; Weinblatt, M.E.; Kavanaugh, A.; Birbara, C.; Kupper, H.; Obermeyer, K.; Faccin, F.
Abstract : Background: Rheumatoid factor (RF) is a prognostic marker of aggressive rheumatoid arthritis (RA); effective disease control may be more difficult in RF positive (+) patients (pts). Some biologic DMARDs have differential response rates based on RF status. Thus, there remains a clinical interest in understanding its impact on clinical response across biologic therapies. Furthermore, a better understanding of the impact of disease duration on clinical outcomes is warranted, particularly in pts who have failed several DMARD therapies. Objectives: To describe the long-term efficacy and safety of ADA in pts with active RA categorized on the basis of RF status and baseline (BL) disease duration. Methods: DE020 was a long-term, multicenter, open-label continuation study of ADA in pts with active RA despite DMARD therapy. This post hoc analysis included observed data through 10 yrs of treatment. Pts were categorized separately on the basis of RF status [negative (-), +] and BL disease duration (≤2 yrs, >2 yrs). Clinical and functional responses were assessed at Yr 10 as the percentages of pts satisfying ACR20/50/70 response criteria, DAS28 (CRP) low-disease activity [LDA, ≤3.2] and remission (<2.6) criteria, and normal physical function (HAQ-DI <0.5). Safety was assessed for the subgroups in terms of adverse events (AEs) for all pts exposed to ADA. Results: The majority of pts were RF(+) (73%) with disease duration >2 yrs (86%). Pts had active disease at BL, irrespective of RF status or disease duration [mean DAS28(CRP) =5.7 for both RF(-) and (+), and 5.8 (≤2 yrs) and 5.7 (>2 yrs)]. RF status did not appear to influence clinical or functional outcomes following 10 yrs of ADA treatment (Table). In contrast and as expected, shorter BL disease duration was associated with greater proportions of pts achieving the more stringent clinical and functional responses, a finding that was most apparent with the proportion having normal function (HAQ-DI <0.5, 61%) at Yr 10. AEs were comparable across the different subgroups and consistent with the known safety profile of TNF inhibitors. Discontinuations due to loss of efficacy were low and comparable across the subgroups. Conclusions: Long-term ADA treatment reduced disease activity and improved overall quality of life in RA pts with an inadequate response to DMARD therapy. In the overall pt population, RF status did not appear to influence the extent of response to treatment with ADA; however, pts with shorter BL disease duration achieved more robust outcomes in greater proportions, underscoring the need to treat pts as early as possible to prevent irreversible damage and loss of function. Disclosure of Interest: D. Furst Grant/Research support from: Amgen, Janssen, Roche, UCB, Consultant for: Amgen, Janssen, Roche, UCB, M. Weinblatt Grant/Research support from: Abbott, Consultant for: Abbott, A. Kavanaugh Consultant for: Abbott, C. Birbara: None Declared, H. Kupper Shareholder of: Abbott, Employee of: Abbott, K. Obermeyer Shareholder of: Abbott, Employee of: Abbott, F. Faccin Shareholder of: Abbott, Employee of: Abbott